2010
DOI: 10.1002/cmmi.408
|View full text |Cite
|
Sign up to set email alerts
|

Localization, mechanism and reduction of renal retention of technetium‐99m labeled epidermal growth factor receptor‐specific nanobody in mice

Abstract: Background: Nanobodies are single-domain antigen binding fragments derived from functional heavy-chain antibodies elicited in Camelidae. They are powerful probes for radioimmunoimaging, but their renal uptake is relatively high. In this study we have evaluated the role of megalin on the renal uptake of anti-EGFR 99m Tc-7C12 nanobody and the potency of gelofusine and/or lysine to reduce renal uptake of 99m Tc-7C12. Methods: First we compared the renal uptake of 99m Tc-7C12 in megalin-deficient and megalin-wild-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 115 publications
(88 citation statements)
references
References 31 publications
7
67
1
1
Order By: Relevance
“…The 99m Tc-RGD4CβL is rapidly cleared from the blood, mainly via the kidneys. This property agreed the typical behaviour of peptides and small proteins whose molecular weight is below the threshold that can be filtered by the glomerular membrane [19]. Meanwhile, 99m Tc-RGD4CβL was eliminated relatively slow in tumor compared with rapid clearance from blood, which means that the prodrug can be administrated when the fusion protein eliminated from normal tissues and the residual in tumor site can release the cephalosporin prodrug to kill tumor cells.…”
Section: Resultssupporting
confidence: 72%
“…The 99m Tc-RGD4CβL is rapidly cleared from the blood, mainly via the kidneys. This property agreed the typical behaviour of peptides and small proteins whose molecular weight is below the threshold that can be filtered by the glomerular membrane [19]. Meanwhile, 99m Tc-RGD4CβL was eliminated relatively slow in tumor compared with rapid clearance from blood, which means that the prodrug can be administrated when the fusion protein eliminated from normal tissues and the residual in tumor site can release the cephalosporin prodrug to kill tumor cells.…”
Section: Resultssupporting
confidence: 72%
“…Strategies to reduce the kidney uptake of radiolabeled protein- or peptide-based vectors have already been investigated intensively. For example, coinfusion with a mixture of 150 mg/kg Gelofusin and 1.2 g/kg L-lysine could reduce renal uptake of a 99m Tc-labeled anti-EGFR nanobody with 45 % 10. Gelofusin also reduced the kidney retention of radiolabeled octreotide analogs to a similar extent 29,30 and a combination of Gelofusin and L-lysine reduced kidney uptake even further 9,31.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation nephropathy has indeed been observed in several patients after PRRT using radiolabeled somatostatin analogues 5-7. Recently, several countermeasures were described to reduce kidney retention of radiolabeled targeting probes 8-10, of which positively charged amino acid and/or Gelofusin coinfusions became standard practice in PRRT. Gelofusin consists of succinylated bovine gelatin molecules and is clinically used as a plasma expander.…”
Section: Introductionmentioning
confidence: 99%
“…Gainkam and coworkers showed that co-administering a mixture of 150 mg/kg Gelofusin and 1.2 g/kg l -lysine reduced renal uptake of a 99m Tc-labeled anti-EGFR nanobody with 45%, as the tumor-to-kidney ratio went up from 0.03 to 0.07 at 1.5 h p.i., in A431 tumor-xenografted mice [72]. Another approach to reduce renal retention of nanobodies consists of mutagenizing the protein sequence at sites that are responsible for interaction with the megalin/cubulin system.…”
Section: Nanobodies: a New Theranostic Tool In Cancer Treatmentmentioning
confidence: 99%